COMPOSITION AND PRINCIPLES OF MARKETING ELEMENTS (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
In order to achieve the goal set in the marketing system, marketing tools, that is, a set of marketing methods and methods, are necessary to influence customers and other subjects. One of such tools is marketing mix, marketing complex. In 1964, Harvard Business School professor Neil Borden was the first to include them in the marketing theory. In this model, the marketing complex in the training system of marketers is called 4 "R" and was proposed by McCarthy in 1960. Four main elements of marketing are distinguished in this model: product, price, place, and promotion.